REALITY THERAPY TRAINING PROGRAM TO REDUCE ACADEMIC PROCRASTINATION BEHAVIOR - Solichah, Novia (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
Academic procrastination is characterized by the inability to manage time, set priorities, focus on the tasks at hand, direct themselves and regulate their actions so that many tasks are delayed. Procrastination is the behavior of delaying in completing academic tasks, this behavior has a bad impact in the future if it is not addressed immediately. The purpose of this study was to test whether training with reality therapy techniques had an effect on reducing procrastination behavior in students. This research method uses a quasi-experimental one group pretest-posttest design. The subjects of this study were 9 students who had high procrastination scores, final year students with more than 10 semesters of study and had taken thesis for more than 2 semesters. The data were analyzed through non-parametric statistical analysis to determine the difference in knowledge scores before and after being given the program. The results showed that training with reality therapy techniques had a significant effect on reducing student academic procrastination behavior (sig 0.008 < 0.05 and Effect size 79%).